Application of Perclose ProGlide closure device in transbrachial endovascular intervention - Peng Zhao; Yao Yao; Quan Yang; Ning Wang; Liang Wang; Qianquan Ma; Wenchao Zhang (Scientific Reports)
Abstract This study aims to assess the clinical efficacy and feasibility of the Perclose ProGlide Suture-Mediated Closure System (Abbott Vascular, Redwood City, CA, USA) for transbrachial access. A total of 100 patients from July 2020 to December 2023 were included in this retrospective study. Among them, 40 patients underwent ProGlide-guided suture closure following brachial artery (BA) puncture, while 60 patients received traditional manual compression. After successful ultrasound-guided puncture of the BA, a sheath of appropriate diameter (5–7F) was inserted. The Perclose ProGlide system was utilized in patients requiring ipsilateral upper limb intravenous infusion or dynamic blood pressure monitoring. All other patients underwent standard manual compression. No significant differences in major complications, including hematoma, pseudoaneurysm, or active bleeding, were observed between the two groups (P = 0.407). Additionally, there were no reported cases of arterial occlusion, ischemia, or venous thrombosis in either cohort. In the manual compression group, three patients required reintervention due to bleeding or hematoma, whereas no such incidents occurred in the ProGlide group (P = 0.151). Two patients in the manual compression group reported long-term numbness around the puncture site, while no similar neurological dysfunction was observed in the ProGlide group (P = 0.243). Although selection bias was present in this retrospective study, the Perclose ProGlide system presents a beneficial closure method for patients undergoing transbrachial access.